The Interdependent Development Concept of Technological, Economic and Management Cycles - Grigorievich Prudskiy, Vladimir; Mikhailovich Oshchepkov, Andrei; Aalexandrovich Zhdanov, Maxim (International Journal of Engineering and Technology, 2018)
The article discusses the relationship between technological and economic cycles and management ones as a specific form of social control, itâ€™s peculiarities in the transition to a neo-industrial economic model.Â Â